PENGARUH PERGANTIAN ASPAL DENGAN 2% GETAH DAMAR TERHADAP SIFAT MARSHALL CAMPURAN AC-BC - Kusmira Agustian; Khairul Anwar (JMTS: Jurnal Mitra Teknik Sipil, 2023)
This study aims to determine the effect of replacing 2% gum resin in asphalt-on-asphalt concrete-binder course (AC-BC) mixtures. The initial step is to examine the physical properties of the asphalt mixture, followed by making samples with several percentages of asphalt to determine the optimum asphalt content (OAC). After OAC was obtained, samples were made again on OAC either without or with 2% gum resin replacement. The OAC obtained for the asphalt mixture without gum resin replacement was 4.75%, while the OAC with 2% gum resin replacement was 4.65%. The stability value of the mixture with 2% gum resin replacement was higher than the mixture without gum resin, namely: 2,276.66 Kg compared to 2,143.92 Kg. Density, void in mineral aggregate (VMA), a void filled by asphalt (VFA), flow, and Marshall quotient values of the two types of mixtures met the required specifications. The results of calculating the durability of the mixture without gum resin replacement were obtained greater than the mixture with 2% gum resin replacement, namely: 93.16% versus 97.03%. This shows that the two types of mixtures can survive and not be damaged when changes in temperature and weather occur. It can be concluded that the use of gum resin as a substitute for asphalt can improve the quality of the asphalt mixture both in receiving repeated traffic loads and in dealing with climate change.